Energy, risk & competitive advantage : the information imperative - Randall, Scott, 1958- (PennWell, 2008)
"Both front-line information gatherers and executives assigned to oversight will find invaluable tools for data analysis, risk analysis, and systemic monitoring. In turn, these tools will allow leaders to put this information into action with confidence."--Jacket